Comparison Between Results of Trabeculectomy With or Without Anti- Vascular Endothelilal Growth Factor in Patients With Neovascular Glaucoma at Undaan Eye Hospital Surabaya, Indonesia: Oral Presentation - Observational Study - General Practitioner - Malika, Rosalia Adriani; Nuradianti , Lydia (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesNew intraocular medication, Anti-vascular endothelial growth factor (Anti-VEGF) agents has beendeveloped in the management of neovascular glaucoma and in glaucoma surgery. But there are nostudies comparing trabeculectomy with Anti-VEGF to no Anti-VEGF treatment in patients withneovascular glaucoma. This study aims to compare decrease of intraocular pressure (IOP) betweentrabeculectomy with Anti-VEGF and without Anti-VEGF in neovascular glaucoma. MethodsThis observational retrospective study comprised 30 medical records of neovascular glaucoma,divided to 15 medical records of patients with anti-VEGF before trabeculectomy and medical recordsof patients operated with trabeculectomy without anti-VEGF, monitored between January 2021 toDecember 2021. Patients with incomplete medical records were excluded. Data collected are age,gender, risk factor, intraocular pressure pre operative, and during 6 months follow-up IOP postoperative. Data analysis uses an Independent T test. ResultsFrom 30 samples, mean IOP in trabeculectomy with anti-VEGF group generally is 12,26 mmHg.Meanwhile, mean IOP in trabeculectomy without anti-VEGF group generally is 16,74 mmHg. Tindependent test between 2 groups shows that there are significant mean difference between themduring 1-5 months follow-up (1 month: p = 0,022; 2 months: p = 0,007; 3 months: p = 0,007; 4months: p = 0,042; 5 months: p = 0,029). ConclusionTrabeculectomy with prior administration of intravitreal anti-VEGF shows good IOP reduction andcan be implemented in NVG patients.